Pembangunan Kampung Iklim Ramah Lingkungan di Jatinegara Kaum Sebagai Bentuk Aksi Adaptasi dan Mitigasi Perubahan Iklim - Iriani, Tuti; Laras Nugraheni, Prastiti (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Iriani T, Nugraheni PL. 2022. Development of an environmentally friendly climate village in jatinegara kaum as a form of climate change adaptation and mitigation action. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 469-479. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The issue of climate change has become a real environmental phenomenon and is recognized as one of the biggest threats to human life. Currently, the earth's surface temperature (global) continues to increase every year. In this regard, the Climate Village Program (PROKLIM) is one of the community-based national program efforts to prevent rising greenhouse gas emissions and prevent the impact of climate change with proactive adaptation and mitigation actions that contribute to national development efforts. The purpose of this activity is to build an environmentally friendly climate village, especially in the RW.01 area, Jatinegara Kaum village. This area in RW.01 is very congested, if it is raining, the access road to residents' houses is full of puddles and lacks of open areas. This community service activity includes socialization, practice, and assistance in making compost and eco enzyme as well as planting 200 trees in pots made from used tires as an application of the mitigation concept. From the results of the activities obtained, it shows that the community is willing to be actively involved in realizing the proklim in the RW.01 area which is indicated by the community being able to process their household waste by separating waste according to its type and processing the waste into compost. In addition, the people of the village of Jatinegara, the RW.01 have also started greening the environment by planting various kinds of plants.